ENFORCEMENT OF REGIONAL REGULATION NO. 2 OF 2018 ON PUBLIC ORDER AND COMMUNITY TRANQUILITY BY SATPOL PP IN TULANG BAWANG REGENCY, LAMPUNG PROVINCE - Alam, Muhammad Dharma (Fakultas Hukum Tata Pemerintahan, 2024)
Land abuse was a prevalent issue in many areas, with frequent cases of unauthorized use of government land and construction of buildings without proper permits. Tulang Bawang Regency's Regional Regulation No. 2 of 2018 was designed to address these issues by regulating public order and community tranquility, specifically focusing on the orderly use of land and buildings. The regulation was enforced by the Tulang Bawang Regency Pamong Praja Police Unit. This research, which employed qualitative methods including observation, interviews, and documentation, evaluated the implementation of Regional Regulation No. 2 of 2018. The findings indicated that while the Pamong Praja Police Unit adhered to procedural standards, the implementation was suboptimal, with many areas still exhibiting disordered land and buildings and insufficient follow-up from local authorities. The research concluded that the Regional Government needed to provide more support to the Pamong Praja Police Unit to enhance the enforcement of regulations and achieve better public order and tranquility in Tulang Bawang Regency. The Pamong Praja Police Unit played a crucial role in monitoring illegal buildings and assisting the Regional Government in enforcing the applicable regulations.